Zr-doped SAPO-34 with enhanced Lewis acidity. (4th February 2022) - Kokuryo, Shinya; Tamura, Kazuya; Miyake, Koji; Uchida, Yoshiaki; Mizusawa, Atsushi; Kubo, Tadashi; Nishiyama, Norikazu
Abstract : Zr-doped SAPO-34 has enhanced Lewis acidity, leading to high catalytic activity for LDPE cracking. Abstract : CHA-type silicoaluminophosphate zeolite (SAPO-34) has been utilized as a functional material in various applications such as reactions and separations due to its unique pore structure and acidity. Various efforts have been made to improve its performance. However, the Lewis acidity of SAPO-34 has not been focused on so far. Herein, Zr-doped SAPO-34 was synthesized by a dry gel conversion using amorphous ZrO2 –SiO2 with highly-dispersed Zr species to control the Lewis acidity of SAPO-34. The Zr-doped SAPO-34 had only highly-dispersed Zr species, which interacted with the frameworks of SAPO-34, while bulky ZrO2 was formed in Zr-loaded SAPO-34 prepared by an impregnation method. The Zr-doped SAPO-34 showed higher catalytic activity in low-density polyethylene cracking than a pristine SAPO-34 and Zr-loaded SAPO-34. The higher catalytic activity is likely to originate from the highly-dispersed Zr species showing Lewis acidity without inactive bulky ZrO2 . This work can provide a new direction for the design of SAPO-34.